1999
DOI: 10.1177/089686089901900412
|View full text |Cite
|
Sign up to set email alerts
|

Once-Daily Intraperitoneal Gentamicin is Effective Therapy for Gram-Negative Capd Peritonitis

Abstract: Objective To report our 3-year experience with the use of once-daily intraperitoneal (IP) gentamicin in the treatment of gram-negative continuous ambulatory peritoneal dialysis (CAPD) peritonitis. Design A prospective cohort study in prevalent CAPD patients. Setting A tertiary care institution. Patients All CAPD patients who presented with new episodes of peritonitis were studied. At presentation with peritonitis, IP vancomycin and gentamicin were administered as empirical therapy. IP gentamicin was given at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…At the dosage currently recommended, the peak gentamicin concentration in dialysis solution is at least 8 times the minimal inhibitory concentration (MIC) of the likely pathogens ( 315 ). Two studies showed that once-daily gentamicin is as effective as continuous dosing for CAPD patients ( 256 , 316 ). However, systemic absorption of intermittent IP gentamicin is highly variable and depends on the peritoneal transport characteristics ( 315 ), and the high systemic absorption of gentamicin in patients with peritonitis and prolonged plasma elimination half-life may lead to systemic accumulation and subsequent toxicity ( 315 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…At the dosage currently recommended, the peak gentamicin concentration in dialysis solution is at least 8 times the minimal inhibitory concentration (MIC) of the likely pathogens ( 315 ). Two studies showed that once-daily gentamicin is as effective as continuous dosing for CAPD patients ( 256 , 316 ). However, systemic absorption of intermittent IP gentamicin is highly variable and depends on the peritoneal transport characteristics ( 315 ), and the high systemic absorption of gentamicin in patients with peritonitis and prolonged plasma elimination half-life may lead to systemic accumulation and subsequent toxicity ( 315 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…Some studies have shown that intermittent dosing of IP vancomycin and gentamicin is as effective as continuous dosing in CAPD patients. 22 , 27 , 28 Although in our center we use intermittent dosing of IP ceftazidime, 2 pharmacokinetic studies demonstrated that a once-daily IP administration of ceftazidime at a dose of 15 to 20 mg/kg can result in subtherapeutic blood levels. To achieve a therapeutic level of ceftazidime, a recommended loading dose of 3 g with maintenance dosing of 1 to 2 g every 24 hours is suggested.…”
Section: We Do Not Dose and Choose Antibiotics Correctlymentioning
confidence: 99%
“…While it has been widely recognized that gram-negative peritonitis, as a whole, is associated with poor outcomes (3), E. coli peritonitis carries an interesting variability in its severity, from relatively favorable outcomes (19,20) to a high incidence of treatment failure despite apparently appropriate antibiotic treatment (11). This notion is further supported by the present study, since the clinical outcomes of E. coli peritonitis in our study were generally better than those reported by Yip et al (21), who examined 153 episodes of monomicrobial E. coli peritonitis that occurred between 1995 and 2009 in a single center in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%